Ice seasons 1996-2000 in Finnish sea areas. Jäätalvet 1996-2000 Suomen merialueilla - Seinä, Ari; Grönvall, Hannu; Kalliosaari, Simo; Vainio, Jouni (Merentutkimuslaitos, 2015)
Sisältää myös toisen artikkelin: Ari Seinä, Hannu Grönvall, Simo Kalliosaari, Jouni Vainio, Patrick Eriksson, Jan-Eric Lundqvist: WMO Sea Ice Nomenclature: terminology for the Baltic Sea in English, Finnish and Swedish. WMOn merijääsanasto: Itämeren termistö englanniksi, suomeksi ja ruotsiksi. WMO havsis terminologi för Östersjön på engelska, finska ja svenska